Não acredito em consumo verde. o reflexo do ceticismo no comportamento de compra do consumidor - Braga, Sergio Silva [UNESP]; Merlo, Edgard Monforte; Da Silva, Dirceu (My University, 2016)
The discussion on green consumption and consequently on green products offered in retail attracts the attention of consumers regarding their consumption style. However, it is important to know whether or not the consumer is indifferent (skeptical) the issue at hand. Thus, this research seeks to know: Does the skepticism produces mediating effect between purchase intent and the declared purchase for green products at retail? The objective of this study was to analyze the influence of skepticism as a mediator for the consumption of green products in retail observing how the consumer perceives this issue in society. To address this issue and meet the proposed objective, a quantitative research through a survey with a sample of 1028 real consumers collected in three Brazilian capitals was performed, Brasilia/DF, Salvador/BA and Belo Horizonte/MG. Data analysis was performed using structural equation modeling through SmartPLS 2.0 M3 software. The result indicates that skepticism has no mediating effect on the relationship between intention to purchase and purchases states, but on the other hand, and compared to other studies, the relationship between purchase intent and declared purchase has increased over time in terms of factor loading and this may mean that the consumer is showing more attentive to issues related to consumption of green products at retail.
I do not believe in green consumption. the reflection of ceticism in consumer purchasing behavior
Keywords: Consumer behavior; Green consumption; Green product; Retail; Skepticism